Expression of GUP1 and GUP2, Saccharomyces cerevisiae glycerol active transport genes - Oliveira, Rui Pedro Soares de (2001)
Poster apresentado no "2nd International Meeting on Cellular Responses to Oxidative and Osmotic Stress. Sensing, Signalling and Gene Expression", realizado na Póvoa de Varzim, Portugal de 7 a 10 de Novembro de 2001.